Some Investigations on a Class of Analytic and Univalent Functions Involving q-Differentiation - Ayotunde Olajide Lasode; Timothy Oloyede Opoola (European Journal of Mathematical Analysis, 2022)
We use the concept of q-differentiation to define a class Eq(β, δ) of analytic and univalent functions. The investigations thereafter includes coefficient estimates, inclusion property and some conditions for membership of some analytic functions to be in the class Eq(β, δ). Our results generalize some known and new ones.